Considering the Process of Debt Collection in Community Corrections: The Case of the Monetary Compliance Unit - Link, Nathan W. (Journal of contemporary criminal justice, 2021)
Monetary sanctions levied on individuals on probation and parole may dramatically influence their ability to reintegrate into the community and to complete their community supervision. Yet very little work has empirically assessed how agencies respond to these obligations. This is critical, given that individuals under community supervision occupy a liminal space: free in the community yet often at risk of violation, rearrest, additional fines, or re-incarceration. In this article, we introduce an approach to the collection and management of monetary sanctions by an adult probation and parole agency in one Pennsylvania county. This specialized department focuses solely on repayment of fines, fees, and costs for a subset of probationers and parolees who have completed all other supervision requirements. We complement the conceptual overview by presenting administrative data on this caseload (N = 5,811) to describe the population under supervision and assess the factors associated with debt amount, having difficulty with repayment, and being the subject of an enforcement action for non-payment. We conclude with a discussion of the advantages and disadvantages of this model compared with historical and other existing models of debt enforcement during community supervision.